2015
DOI: 10.1371/journal.pone.0127057
|View full text |Cite
|
Sign up to set email alerts
|

Use of Autoantigen-Loaded Phosphatidylserine-Liposomes to Arrest Autoimmunity in Type 1 Diabetes

Abstract: IntroductionThe development of new therapies to induce self-tolerance has been an important medical health challenge in type 1 diabetes. An ideal immunotherapy should inhibit the autoimmune attack, avoid systemic side effects and allow β-cell regeneration. Based on the immunomodulatory effects of apoptosis, we hypothesized that apoptotic mimicry can help to restore tolerance lost in autoimmune diabetes.ObjectiveTo generate a synthetic antigen-specific immunotherapy based on apoptosis features to specifically r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 56 publications
5
67
0
Order By: Relevance
“…This conceptual innovation allows us to consider this strategy as a potential platform for the reestablishment of immunological tolerance. In vitro experiments demonstrate that liposomes are phagocytosed by DCs from another experimental model (EAE) inducing the same phenotypic and functional changes in DCs than in the T1D model [8].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…This conceptual innovation allows us to consider this strategy as a potential platform for the reestablishment of immunological tolerance. In vitro experiments demonstrate that liposomes are phagocytosed by DCs from another experimental model (EAE) inducing the same phenotypic and functional changes in DCs than in the T1D model [8].…”
Section: Discussionmentioning
confidence: 89%
“…In this sense, several approaches have been developed [7,20,24]. We have recently shown that apoptotic mimicry by means of liposomes -rich in PS and encapsulating autoantigens -arrest autoimmunity in T1D [8]. Therefore, we hypothesized that by replacing the encapsulated autoantigen, PS-liposomes would show therapeutic effect for other autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When intratumoral dendritic cells bind and ingest PS-expressing cells, they maintain an immature phenotype that prevents the expression of costimulatory molecules required for functional antigen presentation (26,38). Moreover, PS externalized on tumor-derived microvesicles suppresses activation of T-cell responses (39), and administration of PS-expressing liposomes containing insulin restores tolerance in a murine model of autoimmune diabetes (40). Lastly, although chemotherapy induces tumor cell apoptosis, the concomitant expression of PS on these cells (41,42) further suppresses potential immune-associated antitumor responses (43).…”
Section: Introductionmentioning
confidence: 99%